Back to the test: Popper's neglected legacy in bilingual advantage research - Marshall, Samuel G.; Bruce Morton, J. (Frontiers in Developmental Psychology, 2025)
Cognitive developmental science has made unprecedented progress in the last 50 years but has also seen many seminal findings fail to replicate. Adopting the bilingual advantage in children's attention control as a case study, we draw a connection between the replication crisis playing out in selected quarters of our field and a wavering commitment to the principles of classical hypothesis testing. Moving forward, we suggest open-science practices as a way of ensuring scientific hypotheses remain falsifiable and unconfirmed.